Does regulation trade-off quality against inequality? The case of German architects and construction engineers - Davud Rostam-Afschar; Kristina Strohmaier (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2018)
We exploit an exogenous price increase by about 10% for architectural services to answer the question how price regulation affects income inequality and service quality. Using individual-level data from the German microcensus for the years 2006 to 2012, we find a significant reform effect of 8% on personal net income for self-employed architects and construction engineers. This group moved from the second lowest to the highest quintile of the net income distribution. This increase in inequality is associated with a deterioration of service quality. The reform reduced average scores of a peer ranking for architects by 18%.
urn:nbn:de:bsz:100-opus-15312
Keywords: L5; L11; L74; J44; L26; 330; Regulation; Inequality; Wages; Service Quality; Entrepreneurship; Natural Experiment